2018
DOI: 10.1177/0950422218756384
|View full text |Cite
|
Sign up to set email alerts
|

Industrial work placement in higher education

Abstract: For civil engineering undergraduates, short-term industrial work placement provides an invaluable learning experience. Notwithstanding the near-universal endorsement of short-term placement programmes, the resulting experience is rarely articulated through the student voice. This article provides an analysis of 174 questionnaires returned by placement undergraduates studying civil engineering at four higher education institutions in the West of Scotland. The commentary captures industrial placement st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Generic competencies often reported by engineering students as learning outcomes of internship include communication and interpersonal skills, teamwork skills, problem-solving skills, presentation skills, time management skills, critical thinking, adaptability, confidence, independence, and perseverance (Au Yeung et al, 1993;Renganathan et al, 2012). While it has been consistently found in a number of studies (Lock, Bullock, Gould, & Hejmadi, 2009;Najid et al, 2012;Parsons et al, 2005;Tennant et al, 2018) that most engineering students perceived the development of teamwork skills and communication skills from their internship experience, some generic competencies were perceived to be better developed than others. For instance, Lock et al (2009) found that more engineering students perceived the development of teamwork skills (91%) and confidence (90%) than communication skills (77%) and self-motivation (74%).…”
Section: Generic Competencies Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Generic competencies often reported by engineering students as learning outcomes of internship include communication and interpersonal skills, teamwork skills, problem-solving skills, presentation skills, time management skills, critical thinking, adaptability, confidence, independence, and perseverance (Au Yeung et al, 1993;Renganathan et al, 2012). While it has been consistently found in a number of studies (Lock, Bullock, Gould, & Hejmadi, 2009;Najid et al, 2012;Parsons et al, 2005;Tennant et al, 2018) that most engineering students perceived the development of teamwork skills and communication skills from their internship experience, some generic competencies were perceived to be better developed than others. For instance, Lock et al (2009) found that more engineering students perceived the development of teamwork skills (91%) and confidence (90%) than communication skills (77%) and self-motivation (74%).…”
Section: Generic Competencies Developmentmentioning
confidence: 99%
“…Internship refers to credit-bearing work experience in a company or an organization for a continuous period of less than a year (Gardner & Bartkus, 2014). It is well-accepted that work experience is a valuable learning experience for engineering students (Spinks, Silburn, & Birchall, 2006;Tennant, Murray, Gilmour, & Brown, 2018), especially in facilitating their development of generic competencies such as problem-solving skills and collaborative and planning skills (Little & Harvey, 2006). However, compared to learning in the classroom, learning in the workplace is less predictable (Crebert, Bates, Bell, Patrick, & Cragnolini, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This study examines whether and how PLBO might influence student SPB and the psychological underlying mechanisms mediating and moderating such relationships. The study is timely given the call for university graduate self-employment research to promote job creation given the lack of jobs in light of the number of graduates produced yearly (Caines et al, 2019; Douglas and Shephard, 2002; Okolie et al, 2019; Okolie et al, 2021a; Tennant et al, 2018). SPB refers to important precursors of self-employment; it typically involves searching, planning, marshalling and organizing behaviours that students require to be self-employed after graduation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…PLBO enables students to undertake normal job roles with organizations for a period of 6 months to 1 year (Poulter and Smith, 2006; Tennant et al, 2018). It is a special joint programme of universities and industry or business organizations designed to prepare students for paid employment or self-employment, and to equip them with the knowledge and motivation to pursue their employment goals after graduation.…”
Section: Introductionmentioning
confidence: 99%
“…Madichie and Fiberesima, 2021). Previous studies have focused primarily on the links between WPL and the development of employability skills (Chukwuedo and Ementa, 2022; Otache and Edokpolor, 2022) as well as other positive graduate outcomes (Nwosu et al, 2022; Okolie et al, 2021a; Poulter and Smith, 2006; Tennant et al, 2018). However, relatively little is known about the methods of delivery that WPL instructors can adopt to enhance students’ learning experience.…”
Section: The Study Objectivementioning
confidence: 99%